2020
DOI: 10.1167/jov.20.8.2
|View full text |Cite
|
Sign up to set email alerts
|

Individual difference in serial dependence results from opposite influences of perceptual choices and motor responses

Abstract: Natural image statistics exhibit temporal regularities of slow changes and short-term correlations and visual perception, too, is biased toward recently seen stimuli, i.e., a positive serial dependence. Some studies report strong individual differences in serial dependence in perceptual decision-making: some observers show positive serial effects, others repulsive effects, and some show no bias. To understand these contrasting results, this study separates the influences of physical stimuli per se, perceptual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 54 publications
(87 reference statements)
6
50
1
Order By: Relevance
“…This effective facilitation could involve a change in sensitivity based on prior stimuli 21 and/or an orientation-dependent modulation of criterion. 28 Previous classification image literature has assumed that the internal template is stable over time. As such, classification-image experiments typically analyze each trial independently.…”
Section: Discussionmentioning
confidence: 99%
“…This effective facilitation could involve a change in sensitivity based on prior stimuli 21 and/or an orientation-dependent modulation of criterion. 28 Previous classification image literature has assumed that the internal template is stable over time. As such, classification-image experiments typically analyze each trial independently.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found response was key in forming positive serial dependence, it may be not due to the motor system per se. In fact, there are studies showing that motor responses show repulsive serial dependence, that is, a tendency of alternating motor responses between trials (Pape et al., 2017; Pape & Siegel, 2016; Zhang & Alais, 2020). It is possible that the positive serial dependence is the characteristic of working memory in stabilizing representations of the outside world by integrating information over time (Kiyonaga et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is possible that the requirement of making responses helps transfer sensory information into working memory and strengthens the storage of rates in working memory, hence biasing the subsequent rates reproduction. The overall serial dependence may be the weighted average across these serial effects at each stage (Zhang & Alais, 2020), which could be the reason why previous studies found mixed results of serial dependence being repulsive or positive.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why only half had positive serial effects under these conditions, but several reasons are possible. First, many studies ( Bliss et al., 2017 ; Turbett et al., 2019 ; Zhang & Alais, 2020 ) have reported that the magnitude of serial dependence varies considerably between participants, from strong positive effects to clear negative effects. In the current paradigm, the stimulus was presented centrally (necessary to dissociate orientation but not spatial position), rather than peripherally, as in many serial dependence studies of orientation ( Cicchini et al., 2017 ; Fischer & Whitney, 2014 ).…”
Section: Methodsmentioning
confidence: 99%